Manual on Assisted Reproduction 2000
DOI: 10.1007/978-3-642-58341-4_16
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Pregnancies and Initial Follow-up of Newborns Delivered after Intracytoplasmic Sperm Injection

Abstract: Objective.\p=m-\Toanalyze the in vivo development of embryos conceived after intracytoplasmic sperm injection (ICSI), as well as obstetric outcome, occurrence of chromosomal abnormalities, and rate of congenital malformations in neonates born as a result of this treatment.Design.\p=m-\Retrospectivestudy. Setting.\p=m-\University-based in vitro fertilization (IVF)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…33 Intracytoplasmic sperm injection represents an effective treatment for severe male factor infertility such as that observed in patients with CATSPER mutations and is now a routine procedure compatible with normal embryonic development. 34 There are conflicting reports on the risk of congenital birth defects associated with ICSI. A relatively low (4.2%) increased risk of congenital abnormalities for children conceived using ICSI has been reported in the largest multicenter study.…”
Section: Resultsmentioning
confidence: 99%
“…33 Intracytoplasmic sperm injection represents an effective treatment for severe male factor infertility such as that observed in patients with CATSPER mutations and is now a routine procedure compatible with normal embryonic development. 34 There are conflicting reports on the risk of congenital birth defects associated with ICSI. A relatively low (4.2%) increased risk of congenital abnormalities for children conceived using ICSI has been reported in the largest multicenter study.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies did not fi nd a rise in the malformation rate after ICSI [10,11,30,38,40] . However, the number of cases was either very low or there was no control group or the investigation technique was not performed in a standard fashion.…”
Section: Fetal Malformations After Artmentioning
confidence: 87%
“…We included all such studies. This probably did not affect our results as others have shown that the outcome as to MM is the same whether cryopreserved or fresh embryos are used (4)(5)(6). The process of selecting the 19 studies that met our inclusion criteria is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%